The fruit hunters [videorecording (DVD)] - Chang, Yung, 1977-; Campbell, Richard J. (Richard John), 1964-; Aguilar Morán, Juan Fernando; Dalla Ragione, Isabella; Pullman, Bill; Gollner, Adam, 1976- (Docurama Films : Distributed in the U.S. by Cinedigm Entertainment, 2013)
Travels across culture, history and geography to show how intertwined people are with the fruits they eat. The ranks of the fruit-obsessed include adventurers, scientists, fruit detectives and even movie star Bill Pullman, fruit hunters dedicating themselves to searching for and saving rare and exotic fruit, and to creating a Garden of Eden in a world increasingly dominated by industrialized monoculture.